Parenting under pressure: a study of parental maltreatment towards children in the context of the covid-19 pandemic - Fakir Al Gharaibeh; Aisha Abdalla AlMidfa; Fatima Zohra Bettayeb (Cogent Social Sciences)
This quantitative study investigates the impact of Covid-19 on parental behavior towards their children during the pandemic. The study collected data from 765 participants conveniently selected in the United Arab Emirates (UAE), including both fathers and mothers who were Emirati and Non-Emirati residents and had at least one school-age child (3–17 years), through an online survey. The results were analyzed through statistical analyses using SPSS v26. The study found that cyberbullying during distance education had the most significant impact among various forms of child abuse, while neglect had the least effect comparatively. The COVID-19 pandemic had diverse effects on children’s well-being, with the absence of friends being the most significant factor. The pandemic intensified parenting pressures due to increased responsibilities and stress, which significantly impacted children’s emotional and psychological wellbeing. Children’s well-being was particularly affected by the pandemic due to the loss of social connections and the development of appetite disorders. These findings highlight the multifaceted consequences of the pandemic on children’s lives and underscore the importance of tailored, innovative interventions and policies in the UAE to address these issues effectively.